Literature Review Defence Mechanisms Against Distributed Denial of Service Attacks (DDoS) - Tamaela, Jovic Luwis; Tanjung, Muhammad Aditya Febriansyah; Ma’arif, Muhammad Fadhli (JURNAL TEKNOLOGI INFORMASI, 2024)
Distributed Denial of Service (DDoS) attacks, which are a major threat to digital infrastructure, pose a major challenge to computer security in today's digital age. In the context of computer network security, this research investigates various approaches that can be used to protect computer networks from DDoS attacks. The main focus is on approaches to prevent, detect, and resolve DDoS attacks. To reduce the impact of the attack, techniques that use protocol filters, signature detection, and network traffic analysis are essential. In conclusion, efforts to prevent, detect and mitigate DDoS attacks and the implementation of effective security strategies are necessary to protect digital infrastructures from such threats Keywords : Distributed Denial of Service (DDoS) Attacks, Computer security, Prevention, detection and mitigation.